Self-assembled gold coating enhances X-ray imaging of alginate microcapsules1. Issue 6 (14th February 2015) - Qie, Fengxiang; Astolfo, Alberto; Wickramaratna, Malsha; Behe, Martin; Evans, Margaret D. M.; Hughes, Timothy C.; Hao, Xiaojuan; Tan, Tianwei
<x xml:space="preserve">Abstract</x> A simple self-assembled gold nanoparticle coating on alginate microcapsules provides them with enhanced and distinctive contrast enabling positive identification and potential for in vivo tracking during rapid X-ray imaging.